Military Tourism: Prerequisites, Prospects, and Socio-economic Implications: Pariwisata Militer: Prasyarat, Prospek, dan Implikasi bagi Pembangunan Sosial-ekonomi - Alimova Guzal Alisherovna (Academia Open, 2023)
This article examines the development of military tourism and its influence on socio-economic development globally, with a focus on the Commonwealth of Independent States (CIS) countries and Uzbekistan. Employing a historical approach, the study investigates the key prerequisites for the emergence of military tourism, while giving special attention to Uzbekistan's prospects in this sector. A comprehensive mechanism for the development of military tourism is proposed, highlighting the identified problematic aspects and factors hindering its growth. The study also delves into the underlying reasons behind the growing popularity of military tourism in contemporary society. The article concludes by presenting recommendations for fostering the advancement of military tourism, thereby offering valuable insights for policymakers, researchers, and practitioners involved in the tourism industry. Highlights: Historical approach: Analyzing the historical context and factors that have contributed to the development of military tourism. Development in Uzbekistan: Examining the specific case of Uzbekistan and exploring its potential for military tourism. Implications for socio-economic development: Investigating the impact of military tourism on the socio-economic growth of countries and regions. Keywords: Military tourism, Socio-economic development, Prerequisites, Prospects, Uzbekistan